The intrauterine and genetic factors associated with the childhood fracture risk - Parviainen, R. (Roope) (Oulun yliopisto, 2020)
Abstract Childhood fractures are common injuries, but the underlying risk factors arising from the prenatal environment or genetics are not well studied. It is not clear why certain children, without bone-affecting diseases, suffer a larger number of fractures than others. The external reasons, such as hobbies and nutritional issues, explain only part of the difference, particularly among young children. Maternal smoking and alcohol consumption during pregnancy are known to cause detrimental effects to the developing fetus. The purpose of this study is to investigate the possible association of these habits with childhood fractures. In addition, the birth weight and birth length of a child have also been shown to reflect the intrauterine conditions; therefore, the association of these parameters to the pediatric fractures was evaluated in this thesis. We also aimed to examine whether there would be genetic loci associated with fractures in children before school age by using a genome-wide association study. The study material included the Northern Finland Birth Cohort 1986, which is a comprehensive pregnancy-birth cohort that includes all women with the expected date of delivery between July 1985 and June 1986, and their live-born offspring from the two northernmost provinces of Finland. The fracture data was acquired from the National Hospital Discharge Register. We found that maternal smoking during pregnancy was associated with 1.83-fold (95% CI 1.06–3.02) increase and the prenatal alcohol consumption was associated with 2.22-fold (CI 1.09–4.12) increase in the offspring’s risk of suffering an inpatient treated bone fracture before school age. We did not find a significant association between the fracture risk and birth weight or birth length. The genome-wide association study (GWAS) revealed one genetic locus (SNP rs112635931) with significant association (p = 7.28x10-9) to fractures and six loci with suggestive association. Tiivistelmä Murtumat ovat yleisiä vammoja lapsuudessa, mutta niiden genetiikasta ...